Apolipoprotein M—A Marker or an Active Player in Type II Diabetes? - Christoffersen, Christina (Frontiers in Endocrinology, 2021)
Apolipoprotein M (apoM) is a member of the lipocalin superfamily and an important carrier of the small bioactive lipid sphingosine-1-phosphate (S1P). The apoM/S1P complex is attached to all lipoproteins, but exhibits a significant preference for high-density lipoproteins. Although apoM, S1P, and the apoM/S1P complex have been discovered more than a decade earlier, the overall function of the apoM/S1P complex remains controversial. Evidence suggests that the complex plays a role in inflammation and cholesterol metabolism and is important for maintaining a healthy endothelial barrier, regulating the turnover of triglycerides from lipoproteins, and reducing cholesterol accumulation in vessel walls. Recent studies have also addressed the role of apoM and S1P in the development of diabetes and obesity. However, limited evidence is available, and the data published so far deviates. This review discusses the specific elements indicative of the protective or harmful effects of apoM, S1P, and the apoM/S1P complex on type 2 diabetes development. Since drugs targeting the S1P system and its receptors are available and could be potentially used for treating diabetes, this research topic is a pertinent one.